The effect of service quality, food quality and accommodation and facilities on hotel guest satisfaction: a case of three star hotels in Kelantan - Lee, Mei Chee; Mohd Yusof, Mohammad Saiful Amri; Md Tamrim, Mohd Nurazwan; Alias, Noor Hazatul Hasni (2015)
This research finding is based on respondents which are hotel guest around Kota Bharu, Kelantan. The hotel get involved in this study are Royal Guest House, Crown Garden Hotel, Dynasty Inn, Tune Hotel and others. The purpose of this study is explaining the effect of service quality, food and accommodation on hotel guest satisfaction in Kelantan three star hotels. There were 150 hotel guests took part in this study. We collected the data at Pengkalan Chepa areas which are airport, campus, KB mall and Kelantan hotel. We distributed questionnaires to people who have experience stayed at the hotel. Data was analysed by using reliability analysis, descriptive analysis, correlation coefficient and multiple linear regressions. It was found out that the service quality, food quality, accommodation have influence guest satisfaction in three star Kelantan Hotel. We hoped that these findings would help hotelier and people in hospitality industry to know the effect of service quality, food quality and accommodation on hotel guest satisfaction. The limitation for our study is we only focusing our study at hotel in Kelantan and only focusing our study towards hotel business. The last limitation for our study is we only focus our study for three star hotels at Kelantan.